CULINARY BUSINESS STRATEGIES IN THE MIDST OF PANDEMIC OF COVID-19 (Case Study at Pork Star Bali) - Billy Tanius; I Gusti Ayu Ari Agustini (Pusat Riset dan Inovasi Nasional, 2022)
This study aims at finding the existing business implemented by Pork Star Bali to survive during the pandemic of Covid-19. Besides, it aimed at exploring the business strategies that can be implemented by Pork Star Bali. The research method used was descriptive qualitative method by applying SWOT analysis to find out the strategies. Data needed were obtained through interviews and literature study. Based on the analysis, it was found that Pork Star Bali implemented rescheduling work time for all the employees to avoid any laid-off, waiting list strategy to accommodate customers’ interests to enjoy Pork Star Bali foods, and selling vacuum products via e-commerce and Instagram. Meanwhile, the strategies that can be applied in the future by Pork Star Bali are maintaining the quality of products, developing innovative menus and products by utilizing technology based on the market’s trends, opening branch outlets since the market is large, strengthening the online marketing, developing customers’ loyalty by improving the quality and services, and developing staff’s loyalty to avoid any hijacking.